Reading the Ransom Logion in 1 Tim 2,6 and Titus 2,14 with Isa 42,6-7; 49,6-8 - Edwards, J. Christopher (Biblica, 2009)
In this study I argue that the same author reads the ransom logion in 1 Tim 2,6 and Titus 2,14 in light of Isa 42,6-7; 49,6-8. The primary evidences are the parallel between the two i3na clauses in Titus 2,14 and Barn 14,6, as well as the idea of covenant mediator, combined with a universal perspective, in 1 Tim 2,1-7. Taken together, these evidences strongly suggest influence from Isa 42,6-7; 49,6-8.